Pengembangan Problem Based Learning Berbasis Portofolio Untuk Meningkatkan Kemampuan Berpikir Kritis dan Sikap Demokratis - Ahmad Latif; Okpatrioka Okpatrioka (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research was carried out to provide support for learning that develops technology in the learning process of students in schools, especially vocational schools, in order to overcome the low effectiveness of practical learning skills that has occurred in productive subjects. The aim of this research is to prepare an electronic practical worksheet (Jobsheet) that can be proven to be practical, valid & effective in improving students' practical learning skills in vocational schools. This research uses the applied Research and Development method. The target of this research is class X students at An Nur Vocational School. Those related to this research are: material, media and language experts. This research has produced valid, practical and effective products in the development of portfolio-based problem based learning to improve critical thinking skills and democratic attitudes. to improve critical thinking skills and democratic attitudes. Validation from material experts obtained a value of 87.2, media experts 87.1 and language experts 88.3 so that the product developed was in the very valid category, with a practicality level of 83.4 classified as very practical, and effective in improving product assembly with a calculated value > ttable, namely 16.491 > 2.015 or < 0.05.